Staff Use of Force in United States Confinement Settings - Steve J. Martin (Washington University Journal of Law & Policy, 2006)
This Essay focuses on the insidious pattern or practice of prison staffs’ unlawful use of force that is cloaked with or protected by an air of legitimacy or facial validity. It is not uncommon for ostensibly lawful applications of physical force to mask the intentional infliction of punishment, retaliation or reprisal on prisoners. Manufacturing or exaggerating the need to physically control a prisoner is one means by which staff pretextually use force for inflicting punishment on a prisoner. An application of force that is legitimately initiated but which escalates to a level of force disproportionate to the objective risks presented by the inmate can likewise be used pretextually by correctional personnel to punish prisoners. On those occasions in which unnecessary or disproportionate force is applied for the primary purpose of inflicting punishment, retaliation, or reprisal, rather than control, such application of force constitutes de facto corporal punishment regardless of its ostensible justification. Often times the subjects of such force are mentally ill offenders whose behavior, as viewed by inadequately trained officers, is to be punished rather than treated.
Keywords: Correctional personnel; Prison violence; Prisoners; Corporal punishment; Force (Law); Imprisonment; United States